Respostas

  • Usuário do Brainly
2014-05-25T15:59:48-03:00

Δ= 4+48=52  raiz de 52=2√13

x=2+2√13/2= 2(1+√13)/2=  1+√13   e 1-√13      S={1+√13 , 1-√13}

outra

Δ=25-24=1

x=(-5+1)/-2=-4/-2=2         S={2,3}

x=(-5-1)/-2=-6/-2= 3


2014-05-25T16:14:28-03:00
a) 2x²-2x-12=0
▲ = b² - 4.a.c
▲ = (-2)² - 4.2.(-12)
▲ = 4 + 96
▲ = 100

-b +/- 
√▲
    2.a
-(-2) +/- 
√100
       2.2
2+/-10
    4
x' = 2+10 
         4
x' = 3

x" = 2 - 10
          4
x" = 2

b) -x²+5x-6=0
▲ = b² - 4.a.c
▲ = 5² - 4.(-1).(-6)
▲ = 25 - 24
▲ = 1

-b +/- √▲
    2.a
-5 +/- √1
   2.(-1)
(-5)+/-(-1)
    -2
x' = -6
      -2
x' = 3

x" = -4
       -2
x" = 2